Editor's introduction: Innovative dynamical approaches to cognitive systems. (December 2019) - Favela, Luis H.
Abstract: This Editor's Introduction to the Cognitive Systems Research special issue, "Innovative Dynamical Approaches to Cognitive Systems, " has three aims: First, the background and motivation for the topic are stated. Second, overviews of the contributing papers are presented. Third, based on the papers, speculations on future directions in dynamical approaches to the investigation of cognitive systems are presented. Here, the focus is on concepts, data analysis methods, and computational modeling.